Indigenous and Non-Indigenous Unemployment, Employment and Participation Rates Through 2024: Education is Strongly Related to These Three Rates - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development, 2025)
The overall employment picture for the Indigenous population living off-reserve was worse in 2024 than in 2023, and it was also worse in 2023 compared to 2022. They were also worse for non-Indigenous people in 2024, compared to 2023. Unemployment rates were higher, and employment and participation rates were lower. Employment, unemployment, and participation rates have been more favourable for the non-Indigenous population than for the Indigenous population. This has been the case in every year, except one, since 2007, which is the earliest that the data has been available. However, the educational level achieved is a critical factor. When educational levels are higher, unemployment rates are lower, and employment and participation rates are higher. Further, the participation rates for the Indigenous population were higher for each comparable education level than for the non-Indigenous population from 2007 through 2024, except for four years.